Model Komunikasi Pendidikan di Sosial Media Pada Era Perkembangan Teknologi - Faisal Faliyandra (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
The purpose of this article is studying the educational communication model in this technological development era and Ki Hajar Dewantara's theory, so as to find a renewal study of educational communication in the era of technology based on Indonesian education. This research uses a library method or approach (library research), by collecting various data relevant to be carried out in journals, books and other related documents. From the analysis of several documents, explain that Ki Hajar Dewantara's educational theory adheres to some basic foundations of the philosophy of pragmatism and the theory of progressive education. From the two basic foundations, it will be linked to communication theory which is adapted from Osgood and Schraam's Circular theory. So, find the concept of communication of freedom of learning in the era of technological development. DOI: https://doi.org/10.5281/zenodo.3672385